Effect of deep mixed column pattern on the performance of basal reinforced embankment resting on soft soil - Sujata Fulambarkar; Bappaditya Manna; J.T. Shahu (Soils and Foundations)
The deep mixing method (DMM) a soil solidification technique, involves mechanically blending the natural soft soil with a binder to create stiffer soil columns or panel walls, enhancing stability in soft ground areas. In this study, different configurations of deep mixed (DM) columns with a consistent area ratio were tested under vertical loading. Various column patterns, including Square Group Columns (SGC), Longitudinal Tangent Wall (LTW), Transverse Tangent Wall (TTW), and Tangent Grid (TG), were evaluated for their response to stress-settlement, the heaving of the soft clay, and the lateral deformation of the embankment slope. Particle Image Velocimetry (PIV) was employed to analyse ground deformation during the tests. The results show that the LTW pattern has the least, while the TG pattern has the maximum heaving of soft soil and lateral deformation of the embankment slope. The LTW pattern showed the most significant strength improvement, while the TG pattern demonstrated the least enhancement in strength compared to the other patterns. A post-examination of the deformed column was conducted to understand the column failure pattern, and it was noted that the DM column primarily experienced failure due to tilting and bending, indicating that these columns did not fully mobilize their shear strength.